MINAT SISWA TERHADAP KEGIATAN EKSTRAKURIKULER PANAHAN DI SMPIT AL MUMTAZ PONTIANAK - Hadi, Ridho Purnomo; Supriatna, Eka; Gustian, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to known student interest about archery extracurricular at SMPIT Al Mumtaz Pontianak.. The method used is descriptive quantitative research method with the form of survey research and the data collection technique used questionnaires. The sample was taken by random sampling technique that amounted to 50 students. Data were analyzed using descriptive prosentative. The result showed that the percentage of intrinsic factors affecting interest such as desire (67%), leisure time (76%), pleasure (72%), getting friends (42%) and maintaining health (70%) by mean 65.4 %. Meanwhile, the percentage of â€œyesâ€ answer on intrinsic factor indicator which includes the implementation of activity (61%), media (32%), and rewards (52.67%) with the average 48.89%. The conclution of this research is in average, the students interest to archery extracurricular activity is belong to â€œsufficientâ€.Keywords : Extracurricular, interest, archery, SMPIT Al Mumtaz